Faktor-Faktor yang Berhubungan dengan Pengetahuan Kesehatan Reproduksi Remaja Tunanetra di Salah Satu Panti Sosial Jakarta Timur - Satryana Devy Pamungkas; Debbiyantina Debbiyantina; Ani Kusumastuti; Winancy Winancy (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Blind people are also classified according to the time of intimacy. Like blind people from birth or visually impaired at a certain age. This is related to their experience of seeing and allowing them to facilitate learning. Providing information about reproductive health in blind teenagers is still an in-depth study of the effectiveness and process of giving. This study aims to determine the level of knowledge of blind teenagers about reproductive health and whether there is a relationship between the status of disability and the reproduction class that has been run by the social institution. This study uses a cross sectional approach with univariate and bivariate analysis methods. The sample of this study was 40 adolescents between the ages of 10-19 years who were disabled in terms of the blind. The results showed that the majority of respondents had good knowledge (52.5%), when the occurrence of disability in teenagers mostly occurred less than the age of 5 as many as 23 people (57.5%), the participation of adolescents in reproductive health classes was 20 respondent (50%). The results of the bivariate analysis showed that there was no significant relationship between the time of use and the respondents' knowledge about reproductive health (P value 0.491). There is a significant relationship between participation in the reproduction class and the respondents' knowledge about reproduction.